Measurement of the effectiveness of an HIV/AIDS intervention programme on knowledge, attitudes, and behaviour of the South African Polise Service employees - L. Cherian; L.S. Maphoso (AOSIS, 2009)
This study investigated if there was any change in the HIV/AIDS knowledge, attitudes, and behaviour of the South African Police Service's (SAPS) employees of Limpopo province after attending the HIV/AIDS intervention programme. From a population of (N=108) employees, those who attended the HIV/AIDS awareness workshop participated as experimental group (n=51) while those who attended the suicide prevention and disability workshop as control group (n=57). Random sampling method was used to select the above sample. Both workshops were conducted at various places in Limpopo Province. Pre-tests were administered before the workshops while the post-tests were administered after the workshops. The results were analysed using 2 (Group: Experimental versus Control Group) x 2 (Time: Pre-test versus Post-test, a repeated measure) Analyses of Variances (ANOVA). The findings showed that there was a significant change in HIV/AIDS knowledge after employees have attended the HIV/AIDS awareness workshop. There was however no significant change in attitude and behaviour after the HIV/AIDS awareness programme. The study recommends that a one day workshop is not enough to change attitude and behaviour. It also recommends that a follow up in the form of delayed post-test is required to investigate if the behaviour of the members who promised to change positively had actually changed as behaviour changes cannot manifest in a one day workshop. This can also serve as a suggestion for further research.